The status of sow welfare in selected districts of Uganda - Dione, Michel M.; Oba, Peter; Nsadha, Zachary; Kassahun, A.; Knight-Jones, Theodore J.D.; Doyle, Rebecca (International Livestock Research Institute, 2022)
Objective The pig sector in Uganda is among the fastest growing livestock sectors and is characterized by low productivity from limited resources and veterinary support. As the welfare status of pigs in the system is unknown a cross-sectional welfare assessment was carried out in four districts in central Uganda (Masaka, Mukono, Mpigi and Wakiso) to identify issues requiring action. Materials and methods Data were collected from 270 pig farms. Data on animal-based indicators (body condition and physical injuries) and resource-based indicators (housing and water supply) were obtained from physical assessments of pigs and farm facilities. Management data (morbidity and mortality) and demographic details were collected from farmer interview. We present sow results as they are the highest value animal of the herd, both raising piglets and requiring resource investment. Results Across all farms, sow mortality was 2.5%. Animal-based indicators identified 9% of sows with diarrhea, 7.6% with lameness and 92% dry or lactating were found to be ‘skinny’ (body condition score≤2). All of these are indicative of underperforming sows that may be at risk of low litter indices and shorter productive lives. Sow behaviour was restricted in 19% of cases, and while 93% of sows had access to continuous water, only 48.8% received clean water, which creates a risk of disease spread. Of reported health issues, 20% farms reported sows experiencing stillbirths, 15% ill thrift, 12.5% respiratory issues and 10.8% gastrointestinal issues. Conclusion These welfare issues indicates that a proportion of sows were in pain, discomfort and potentially hungry, which in turn negatively impact on owner livelihoods from wasted resources and opportunities. Future interventions focusing on herd health should focus on diseases and poor nutrition. Interventions that provide access to clean water and optimum living space that give sows the ability to move more freely are also required.